2016
DOI: 10.1002/2015jd024383
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the near‐surface atmosphere over the Ross Ice Shelf, Antarctica

Abstract: Two years of data from a 30 m instrumented tower are used to characterize the near-surface atmospheric state over the Ross Ice Shelf, Antarctica. Stable stratification dominates the surface layer at this site, occurring 83% of the time. The strongest inversions occur for wind speeds less than 4 m s À1 and the inversion strength decreases rapidly as wind speed increases above 4 m s À1 . In summer unstable stratification occurs 50% of the time and unstable conditions are observed in every season. A novel aspect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(68 citation statements)
references
References 44 publications
(87 reference statements)
10
57
1
Order By: Relevance
“…In this case, the near‐surface temperature inversion may reach values up to 25 K between 10 m and the surface, as the coupling between the air and the snow is (essentially) of radiative origin. Riordan () (see also Hudson and Brandt, ) and Cassano et al () (see also Wille et al, ) identified similar wind speed thresholds that distinguish a SBL regime with strong near‐surface inversions from a regime with weak near‐surface inversions at the South Pole and over the Ross ice‐shelf, respectively. This suggests that the two‐regime behavior of the SBL may prevail over a large part of the Antarctic continent where the surface slope is weak (ice‐shelves, Plateau).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the near‐surface temperature inversion may reach values up to 25 K between 10 m and the surface, as the coupling between the air and the snow is (essentially) of radiative origin. Riordan () (see also Hudson and Brandt, ) and Cassano et al () (see also Wille et al, ) identified similar wind speed thresholds that distinguish a SBL regime with strong near‐surface inversions from a regime with weak near‐surface inversions at the South Pole and over the Ross ice‐shelf, respectively. This suggests that the two‐regime behavior of the SBL may prevail over a large part of the Antarctic continent where the surface slope is weak (ice‐shelves, Plateau).…”
Section: Introductionmentioning
confidence: 99%
“…The statistics of summertime inversion properties over Dronning Maud Land, Antarctica, were qualitatively close to those reported in previous studies based on six Antarctic radiosonde stations during a 20 year period (Zhang et al ., ), radiosonde soundings over sea ice in the western Weddell Sea in autumn and early winter (Andreas et al ., ), microwave radiometer‐based inversion measurements at Dome C (Pietroni et al ., ), and data from a 30 m instrumented tower (Cassano et al ., ). In all these studies, including ours, the inversion occurrence was high.…”
Section: Resultsmentioning
confidence: 97%
“…Nigro et al used SOM to characterize seasonal variability of near‐surface wind speeds. Cassano et al used a similar approach to extract patterns of near‐surface temperature inversion and diagnosed their relationships with observed surface wind speeds and simulated sea‐level pressure. In a follow‐up work, Nigro et al systematically utilized the SOM approach to validate the WRF model‐based Antarctic Mesoscale Prediction System (AMPS) against the observational dataset.…”
Section: Self‐organizing Mapsmentioning
confidence: 99%
“…Furthermore, the total number of final clusters (could be primes or nonprimes) are determined in a completely automated manner; no ad hoc prescription is needed. This automation makes the proposed methodology more advantageous compared with the previous application of SOMs to identify patterns in near‐surface or boundary layer wind data …”
Section: Self‐organizing Mapsmentioning
confidence: 99%
See 1 more Smart Citation